PENGARUH PROFITABILITAS, MANAJEMEN LABA DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015 - 2016) - Minanari Minanari (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The purpose of this research is to know the influence of Profitability to firm’ Value, Dividend Policy to firm’s Value and earning management to firm’s Value. In this study Profitability is measured by ROE, Dividend Policy with DPR and Earnings management with. The data used in this study is the annual financial statements of consumer goods sub-company listed on the BEI for 2 periods from 2015 and 2016. The analysis method used is multiple linear regression with normality test, autocorrelation test, multicolinearity test, glejsertest, heterocedasticity test, R test, F-test, T test. The results showed that Profitability has a significant influence on firm’s Value, Dividend Policy has a significant influence on firm’s Value and Debt Policy has a significant influence on firm’s Value.